Knowledge management-based approach for inter-organisational collaborative processes modelling. (22nd February 2021) - Semar-Bitah, Kahina; Boukhalfa, Kamel
Nowadays the current market is in evolution, organisations must work together to ensure their survival. The collaboration partners are heterogeneous and incompatible, which makes the interaction and exchange between them complicated, and requires new technologies to support them. This paper presents a knowledge management-based approach for inter-organisational collaborative processes IOCP modelling. Ontologies represent an effective solution to deal with the heterogeneity and incompatibility problems in different domains. Collaboration ontologies provide a way to promote its modelling. In this domain, there are only few ontologies which cover it partially. The developed system is composed of three part: 1) gathering and formalising collaborative network knowledge; 2) storing knowledge in a knowledge-based to infer the collaborative process model; 3) the IOCP modelling. The heart of this knowledge-based system is a modular ontology conceived to cover as maximum as possible the collaboration domain. The proposed system was conceived as a part of a collaborative platform allowing the modelling of the IOCP in a generic way.